JURIDICAL STUDY OF STATE ADMINISTRATIVE COURT RULING RELATED TO IMMIGRATION PREVENTION (CASE STUDY NUMBER: 219/G/2017PTUN-JKT SETYA NOVANTO VS. DIRECTOR GENERAL OF IMMIGRATION) - Yogi Prabowo; Taufiqurrohman Syahuri (Journal of Law and Border Protection, 2023)
Prevention means temporary prohibition of person from exiting from the Territory of Indonesia based on particular Immigration reasons or others prescribed by the Law. In the case of immigration prevention against Setya Novanto ordered by the Chairman of the Corruption Eradication Commission (KPK), a lawsuit was filed to the Administrative Court and recorded in Decision Number: 219/G/2017/PTUN-JKT. This research was conducted to answer the following questions: 1) What were the legal considerations of the Judges in issuing Decision Number: 219/G/2017/PTUN-JKT? 2) How was the analysis of the State Administrative Court Decision Number: 219/G/2017/PTUN-JKT? and 3) What were the recommendations for resolving legal issues in administrative disputes within the Directorate General of Immigration? This study used a normative legal research approach, analyzing secondary data in the form of legislation and literature. The research results concluded that the Prevention carried out by the Director General of Immigration was in accordance with the authority specified in legislation and had fulfilled the General Principles of Good Governance. Therefore, the Judges rejected the Plaintiff's lawsuit in its entirety. However, the Defendant's exception was not fully accepted by the Judges, highlighting the need for improvement in resolving administrative disputes within the Directorate General of Immigration to achieve greater quality and professionalism